Syphilis-Related Eye Disease Presenting as Bilateral Papilledema, Retinal Nerve Fiber Layer Hemorrhage, and Anterior Uveitis in a Penicillin-Allergic Patient - Jamie Dietze; Shane Havens (Case Reports in Infectious Diseases)
Purpose. Treponema pallidum is known as the “great masquerader” for its many presentations and ocular findings in patients who are infected and develop secondary and tertiary stage of syphilis. Syphilitic ocular manifestations include uveitis, chorioretinitis, retinitis, vasculitis, vitritis, and panuveitis all with or without decreased visual acuity. Human immunodeficiency virus (HIV) is known to expedite the progression of syphilis when patients are coinfected, thus compounding the potential ophthalmic presentations. This report summarizes the presentation, management, and clinical course of a patient with known HIV and penicillin allergy that presented with bilateral optic nerve edema, retinal hemorrhages, and iritis without vision loss.